2020
DOI: 10.1002/cncr.32737
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome, metabolic components, and their relation to the risk of pancreatic cancer

Abstract: BACKGROUND: Components of the metabolic syndrome (MetS), such as elevated fasting glucose levels and abdominal obesity, have been suggested as potential risk factors for pancreatic cancer. However, data are still insufficient to assure the influence of MetS on incident pancreatic cancer. The objective of the current study was to investigate the association between MetS, metabolic components, and the risk of pancreatic cancer. METHODS: In the Korea National Health Information Database, 223,138 individuals who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 30 publications
(31 reference statements)
1
34
1
Order By: Relevance
“…However, we found no association of obesity with survival in PC, contrary to other studies that showed that obesity is associated with poorer survival [43,44,48]. Previous reports proved a 31-47% increased risk of PC patients with metabolic syndrome [21,49,50], but this was not confirmed in our study. The prevalence of the metabolic syndrome in population with cardiovascular diseases in Romania is up to 40% [51], but recent data in general population are lacking.…”
Section: Discussioncontrasting
confidence: 99%
“…However, we found no association of obesity with survival in PC, contrary to other studies that showed that obesity is associated with poorer survival [43,44,48]. Previous reports proved a 31-47% increased risk of PC patients with metabolic syndrome [21,49,50], but this was not confirmed in our study. The prevalence of the metabolic syndrome in population with cardiovascular diseases in Romania is up to 40% [51], but recent data in general population are lacking.…”
Section: Discussioncontrasting
confidence: 99%
“… 88 The last important piece of the puzzle of environmental factors that may potentially cause exposition to the more frequent occurrence of MetS is air pollution, as demonstrated in the research by, for example, Zhang et al, 89 Yang et al 90 or Matthiessen et al 91 MetS is associated with the development of many other diseases. Available epidemiological and laboratory data indicate that MetS is a potential risk factor for developing certain types of cancers 92 such as colorectal, liver, pancreatic and postmenopausal breast cancer. 93 It has been postulated that the link between MetS and cancer is due to obesity, high blood glucose and other components of MetS.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] The National Cholesterol Education Program's Adult Treatment Panel ш (NCEP: ATP ш), World Health Organization (WHO) and International Diabetes Federation (IDF) employ this syndrome to highlight the risk of individuals developing cardiovascular disease (CVD) and type 2 diabetes (T2DM). 1,4 Moreover, MetS increases mortality due to CVD, 1,5,6 and is associated with the risk of certain types of cancers, 7 such as colorectal cancer, 8 pancreatic cancer, 9 and breast cancer. 10 Although different countries or organizations have recommended different criteria for the definition of MetS, abdominal obesity and insulin resistance are believed to be at the core of most cases of MetS.…”
Section: Introductionmentioning
confidence: 99%